(untitled) (Terr@ Plural, 2019)
Dr. Steward Pickett is one of the pioneers of modern American urban ecology. He is a Distinguished Senior Scientist at the Cary Institute of Ecosystem Studies, in Millbrook, New York. His research focuses on the ecological structure of urban areas and the changes in vegetation through time after disturbance. He believes that ecological knowledge about cities is crucial for both improving the environment and residents’ wellbeing. He has written books on spatial patterns and their changes in ecology, humans as a part of ecosystems, conservation, how to connect ecology with urban design, and linking ecology with ethics.